A GSS process to generate new product ideas and business concepts. (27th January 2009) - Elfvengren, Kalle; Kortelainen, Samuli; Tuominen, Markku
The paper introduces a process for brainstorming new product ideas and business concepts. The developed process utilises a group support system. It aims to enhance the innovation process and the transfer of knowledge inside a company by offering effective means for cooperation. The paper reports the experiences and findings of using the developed process in business cases.